Physical Qualities and Elements of Streets in the Context of Royal Town in Malaysia - Ismail, WNW; Ja'afar, NH; Harun, NZ (Aesthetics Media Services-Aesthetixms, 2024)
Streets are the basic elements in the urban structure and it characterized the townscape and image of the town. The street provides a link between buildings, both within the street, and in the town at large. Streets and buildings must be appropriate to, and unique to, the particular town in which they are located. This article is based on the findings of a doctoral research examining characteristics of street from the aspect of building appearance in the royal town of Kuala Kangsar. Mixed methodology approached are adopted using the triangulation design through the combination of quantitative data with qualitative data to further analyze the relations between them and subsequently validated by focus group discussions. The study found that building is a key component that forms the character of a street and it is contributed by physical qualities such as attractiveness,visibility and human scale. These physical qualities are contributed by physical elements namely building design, building skyline, building continuity and consistency, vertical elements, appearance of civic building, marker sequences, building scale and enclosure. While each of these elements are influenced by factors such as building location,building function, building age, building height and size, building form, building openings, roof form, architectural style, facade treatment and decorations, building signage, street width, five-foot walkway and quality of view. The paper concludes by establishing that street characteristics has a significant contribution in preserving the identity of the royal town therefore it should be considered for the improvement and refinement of existing guidelines regarding the physical design of streets in the royal towns of Malaysia.